If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -1(2a + -6) = 0 Reorder the terms: 12 + -1(-6 + 2a) = 0 12 + (-6 * -1 + 2a * -1) = 0 12 + (6 + -2a) = 0 Combine like terms: 12 + 6 = 18 18 + -2a = 0 Solving 18 + -2a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + -2a = 0 + -18 Combine like terms: 18 + -18 = 0 0 + -2a = 0 + -18 -2a = 0 + -18 Combine like terms: 0 + -18 = -18 -2a = -18 Divide each side by '-2'. a = 9 Simplifying a = 9
| 2e+10=6d-10 | | 6/7x-9=7 | | 10b-3b-7=7 | | 6g/f=h | | 109-32=77 | | 7(x+2)=56 | | 525.00+5x=1500 | | -2(b+2)-5(2b-3)=3 | | 1/5(5n)=1/5(80) | | 3-v=18 | | 10(2p+3)=50 | | 2x-1/5=x+3/4 | | 37+7=-6y-56 | | 525.00+5x=0 | | Y+23=4y-2 | | -3t+1+7=6t-3+2t | | 5/9x=4/9x+9 | | p=q/r | | -3+y=4 | | 5/8p=9/4-3/8 | | 3y=14+4 | | 4d=-3-9 | | 4/7=21/x-3 | | 14=p/2+5 | | 0.5(8y-6)=-15 | | 5n=71+9 | | 13y(2y)+x=30 | | 8x+6=48 | | 2y^-2/3^-1 | | 12x^4-4x+8/4x | | 54=6(7+n) | | f=5(9+4)-8 |